Insect ectoparasites on wild birds in the Czech Republic during the pre-breeding period - Sychra, O; Literák, I; Podzemný, P; Harmat, P; Hrabák, R (Parasite (Paris, France), 2011)
Wild passerine birds (Passeriformes) from the northeastern part of the Czech Republic were examined for ectoparasites during the pre-breeding period in 2007. Two species of fleas of the genera Ceratophyllus and Dasypsyllus (Siphonaptera: Ceratophyllidae), and 23 species of chewing lice belonging to the genera Ricinus, Myrsidea, Menacanthus (Phthiraptera: Menoponidae), Brueelia, Penenirmus, and Philopterus (Phthiraptera: Philopteridae) were found on 108 birds of 16 species. Distribution of insect ectoparasites found on wild birds during pre-breeding was compared with previous data from the post-breeding period. There was no difference in total prevalence of chewing lice in pre-breeding and post-breeding periods. Higher prevalence of fleas and slightly higher mean intensity of chewing lice were found on birds during the pre-breeding period. There was a significant difference in total prevalence but equal mean intensity of chewing lice on resident and migrating birds.
Keywords: Breeding; Time Factors; Prevalence; nemoci ptáků; Insecta; Phthiraptera; Animals; ptáci; Birds; časové faktory; migrace zvířat; infestace ektoparazity; Česká republika; Czech Republic; prevalence; hmyz; Animal Migration; Passeriformes; chov; Siphonaptera; Bird Diseases; Animals, Wild; zvířata; divoká zvířata; Ectoparasitic Infestations